2024
DOI: 10.3390/ani14060859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feed Ingredients with Different Protein-to-Fat Ratios on Growth, Slaughter Performance and Fat Deposition of Small-Tail Han Lambs

Qin Li,
Guishan Xu,
Dong Yang
et al.

Abstract: The purpose of this study was to investigate the effects of feed ingredients with different protein-to-fat ratios on growth, slaughter performance and meat quality of Small-Tail Han lambs. Forty-five Small-Tail Han lambs (♂) (BW = 34.00 ± 2.5 kg, age = 120 ± 9 d) were randomly divided into groups with three different experimental treatments: (1) PF 5, with the ratio of protein to fat (CP:EE) of 50 to 5; (2) PF10, CP: EE = 50:10; (3) PF20, CP: EE = 50:20. Each treatment group had 15 lambs, and each sheep was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…The result could be attributed to interaction effect of the ingredients. Similar with the present study result, Li et al (2024) reported the inconstant trend in weight gain. According to their finding, the daily weight gain is dependent on the ingredient inclusion ratio effect (the protein: fat) than the total supplement amount.…”
Section: Discussionsupporting
confidence: 92%
“…The result could be attributed to interaction effect of the ingredients. Similar with the present study result, Li et al (2024) reported the inconstant trend in weight gain. According to their finding, the daily weight gain is dependent on the ingredient inclusion ratio effect (the protein: fat) than the total supplement amount.…”
Section: Discussionsupporting
confidence: 92%